Using acoustic recording units to investigate the effects of logging of indigenous trees in the Amathole forests, South Africa on Cape Parrot Poicephalus robustus breeding and the presence of three primary cavity-excavating bird species. (24th April 2023) - Rea, Matthew; Elliot, Julia; Carstens, Johann C.; Leaver, Jessica; Carstens, Kate; Wimberger, Kirsten; Cherry, Michael I.
Summary: The Amathole forest complex is the breeding stronghold of the endemic and vulnerable Cape Parrot Poicephalus robustus, and is also one of only two forest complexes in South Africa formally harvested for timber. The aim of this study was to determine if formal harvesting of indigenous trees, primarily the two yellowwood species Afrocarpus falcatus and Podocarpus latifolius, in 9 of 16 Amathole forests has had any effect on the presence of Cape Parrots and three primary nest-excavating species, as well as on parrot breeding. The study used logging data from the past 25 years (1997–2021) as well as data collected by acoustic recording units over two breeding seasons from 2019 to 2021. Cape Parrots were present in 15 of 16 forests, but breeding calls were identified in only seven forests: five in logged and two in unlogged forests. Fourteen of the forests harboured all three primary excavators: Knysna Woodpecker Campethera notata, Olive Woodpecker Dendropicos griseocephalus, and Red-fronted Tinkerbird Pogoniulus pusillus. The last two species were absent from the adjacent Mount Thomas and Kologha forests, respectively, in which parrots were present, but no breeding calls were recorded. Logging of yellowwoods was not found to affect parrot breeding. However, due to the overlap between preferred parrot breeding sites and preferred trees for harvesting, we recommend that harvesting in the five harvested forest blocks where parrot breeding occurs be limited to tree falls, with no standing dead, dying, or damaged trees harvested, to ensure that potential nesting trees are not harvested.